2021
DOI: 10.1177/14034948211058544
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood family background predicts meal frequency behaviour in children: Five-year follow-up study

Abstract: Aims: Childhood nutrition patterns have an important role in later health. We studied the role of family type, other family background factors and their changes over a five-year follow-up with respect to meal frequency among children. Methods: Longitudinal data were collected in 2007–2009 and 2013–2014. A nationally representative sample of Finnish children ( n = 1822) aged 0.5–5 years at baseline and 5–10 years at follow-up and their families were used. The participation rate was 83% at baseline and 54% at fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In childhood, family and living environment play important roles in adopting, establishing and promoting healthy lifestyles through role modelling and support for engaging in healthy lifestyle habits [33][34][35][36][37]. Previous Finnish studies have shown a socioeconomic gradient between parents' SEP and lifestyle habits in childhood and adolescence [36,[38][39][40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In childhood, family and living environment play important roles in adopting, establishing and promoting healthy lifestyles through role modelling and support for engaging in healthy lifestyle habits [33][34][35][36][37]. Previous Finnish studies have shown a socioeconomic gradient between parents' SEP and lifestyle habits in childhood and adolescence [36,[38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…In childhood, family and living environment play important roles in adopting, establishing and promoting healthy lifestyles through role modelling and support for engaging in healthy lifestyle habits [33][34][35][36][37]. Previous Finnish studies have shown a socioeconomic gradient between parents' SEP and lifestyle habits in childhood and adolescence [36,[38][39][40]. A systematic review identified several factors, such as parental obesity, child-care attendance, and high TV viewing time, which mediate the relationship between SEP and childhood overweight and obesity [41].…”
Section: Discussionmentioning
confidence: 99%